2017
DOI: 10.1021/acs.iecr.6b04538
|View full text |Cite
|
Sign up to set email alerts
|

Embedding Graphene Nanoplates into MIL-101(Cr) Pores: Synthesis, Characterization, and CO2 Adsorption Studies

Abstract: In this research, the equilibrium and dynamic adsorption studies of the CO2 upon the MIL-101­(Cr) metal–organic framework (MOF) as well as its GNP hybrid composites, the MIL-101­(Cr)/GNP, were performed. First, the hybrid composite samples were synthesized by adding various amounts of GNP in an in situ manner during the preparation of the MIL-101­(Cr). The prepared materials were characterized through several physicochemical analyses, including powder X-ray diffraction (PXRD), adsorption of nitrogen at 77.4 K,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 51 publications
(9 citation statements)
references
References 35 publications
(86 reference statements)
0
9
0
Order By: Relevance
“…Adsorption kinetics determines the efficiency of an adsorbent in dynamic processes and its endurance in large adsorbate flow. , Fast adsorption kinetics is one of the most critical properties of adsorbent since it can determine residence time required for the completion of the adsorption process, adsorption bed size, and, consequently, unit capital costs which are all essentially associated with the rate of adsorption. Many researchers have attempted to clarify the information that can be deduced from adsorbent–adsorbate interactions, and consequently a series of established models have been introduced.…”
Section: Methodsmentioning
confidence: 99%
“…Adsorption kinetics determines the efficiency of an adsorbent in dynamic processes and its endurance in large adsorbate flow. , Fast adsorption kinetics is one of the most critical properties of adsorbent since it can determine residence time required for the completion of the adsorption process, adsorption bed size, and, consequently, unit capital costs which are all essentially associated with the rate of adsorption. Many researchers have attempted to clarify the information that can be deduced from adsorbent–adsorbate interactions, and consequently a series of established models have been introduced.…”
Section: Methodsmentioning
confidence: 99%
“…The reason why ZJNU-54 exhibits a higher uptake of CO 2 than CH 4 is difference in the isosteric heat of adsorption. The value of isosteric heat of adsorption for CO 2 and CH 4 at low coverage are 24.7 and 16.8 kJ mol -1 , suggesting that CO 2 is adsorbed more strongly in ZJNU-54 than CH 4 . Another strategy is post-synthesis method, that is, to chemically modify MOFs after the formation of MOFs crystals.…”
Section: Ligand Functionalizationmentioning
confidence: 95%
“…Besides, the Q st value of CO 2 adsorption should be increased to a certain degree that minimized the energy penalty for regeneration. Yeganegi et al have done theoretical study on the effect of lithium cation on the adsorption and sepearation of CO 2 , CH 4 , and H 2 on a Zn 2 (NDC) 2 (diPyNI). The results indicated that the selectivity of CO 2 /H 2 on MOF was higher than that of CO 2 /CH 4 at room temperature and pressure up to 50 bar [16].…”
Section: Ligand Functionalizationmentioning
confidence: 99%
“…K F (mmol.g 1 .MPa 1=n ) is the Freundlich constant and n is surface heterogeneity parameter of the solid. The constant K F is an approximate indication of the adsorption capacity, while 1=n is a function of the strength of adsorption [26]. However, K F and n are characteristic parameters of the sorbent-sorbate system that should be determined through tting with the experimental data.…”
Section: Ch 4 Equilibrium Adsorption Modelingmentioning
confidence: 99%